Strategy for Strengthening the Capacity of Government Internal Supervisory Apparatus to Increase the Effectiveness of Internal Supervision - Nibel, John Sansri; Yunus, Muhammad; Syahribulan, ‎ (KnE Social Sciences, 2025)
This study aims to evaluate the capacity of the government’s Internal Supervisory Apparatus (APIP) and identify the main challenges that hinder the effectiveness of internal supervision at the South Sulawesi Police Inspectorate. In addition, this study also aims to formulate a strategy to strengthen the capacity of APIP to support more transparent, accountable, and professional police governance. This study uses a qualitative approach with a case study method, thematic analysis, and NVivo 12 Plus assistance. Data were collected through in-depth interviews, document studies, and observations. The findings of this study indicate that the effectiveness of internal supervision of APIP in the South Sulawesi regional police is hampered by various challenges, such as limited human resource competency that has not fully mastered risk-based audit techniques and information technology, lack of policies that are responsive to dynamics in the field, limited use of technology in supervision, and low cross-unit coordination that result in inconsistencies in reporting and follow-up of recommendations. Therefore, comprehensive reform is needed by strengthening human resource capacity, developing adaptive policies, and implementing more effective technology and coordination systems. Capacity-building strategies include enhancing competence through ongoing training and professional certification, preparing integrated standard operating procedures (SOPs), and utilizing information technology to improve the efficiency and transparency of supervision. These efforts are expected to foster more effective, transparent, responsive, and results-oriented internal supervision, thereby supporting the achievement of better governance.